Welfare Implications of Democratization in Content Creation: Generative AI and Beyond - Zou, Tianxin; Shi, Zijun (June); Wu, Yue (Journal of Marketing Research, 2026)
The rise of content-creation technologies such as generative artificial intelligence (GenAI) has reshaped the way people produce and consume content. These technologies democratize content creation, enabling inexperienced individuals to generate content that rivals the quality produced by professionals. This article adopts a game-theoretic model to study how the democratization of content creation affects welfare. While the content-democratization technology can assist low-quality creators in improving their content quality, it can precipitate a flood of such content in the market and crowd out high-quality content production, leading to welfare losses. An incremental technology development with a small reduction in the quality gap can hurt individual consumers and all creators, leading to a lose-lose market outcome. In contrast, a development with a high reduction in the quality gap benefits individual consumers and all creators, leading to a win-win outcome. Furthermore, when platforms can more effectively screen content and promote high-quality content, welfare rises, but the content-democratization technology is more likely to reduce welfare. The findings help explain the distinct impacts of content democratization in different industries.